3D high resolution anorectal manometry in functional anorectal evaluation - Ihnát, P; Vávra, P; Guňková, P; Pelikán, A; Zonca, P (Rozhledy v chirurgii, 2014)
INTRODUCTION: Anorectal manometry is a diagnostic tool designed for the evaluation of functional parameters and assessment of anorectal activity coordination. In the last decade, the development of 3D high-resolution (HR) manometry and its expansion in experimental and clinical settings has been evident. Literature search (in the MEDLINE and PubMed databases) focusing on studies about 3-dimensional HR manometry was performed. The aim of this paper is to offer an overview of the current state of the art of manometry while concentrating on indications, protocol of the procedure and applicability of this examination in clinical practice. RESULTS: Development of solid catheters with miniaturized semiconductor sensors has enabled very precise measurement (high resolution) and creation of anorectal 3D pressure models. In comparison with water-perfused manometry systems, this method offers more accurate and more detailed data that can be employed in functional disorders assessment. The indications for anorectal manomery are symptoms of faecal incontinence and functional constipation. This modality can also be used in biofeedback therapy, in functional anorectal pain and when assessing patients undergoing continent rectal resection. The HR manometry protocol should comprise the measurement of anorectal resting pressures, the squeeze manoeuvre, the bear down manoeuvre, the cough reflex test, the rectoanal inhibitory reflex examination, rectal sensitivity testing and rectal compliance measurement. Processed data are fundamental in determining an individually tailored treatment plan for patients suffering from anorectal functional disorders. CONCLUSION: Anorectal 3D HR manometry presents a valuable diagnostic modality offering a new dimension in anorectal function understanding and can reveal new pathophysiologic mechanisms of anorectal functional disorders.
Keywords: manometrie; anální kanál; Anal Canal; Imaging, Three-Dimensional; Fecal Incontinence; zácpa; Rectum; zobrazování trojrozměrné; Pressure; tlak; Constipation; Humans; Manometry; rektum; lidé; fekální inkontinence